The Effectiveness of Blooket in Teaching Arabic Vocabulary to Students of Pembangunan Islamic Middle School in Tangerang - Ari Aprian Harahap; Muhamad Ihwanul Muslimin; Ubaid Ridlo (Al-Muyassar: Journal of Arabic Education, 2025)
This research aimed to reveal the effectiveness of using the Blooket method (Blooket) In teaching Arabic vocabulary to students of Pembangunan Islamic Middle School in Tangerang. This research coincided with the implementation of the Arabic language strengthening program in the school, as the program seeks to improve the students’ Arabic language skills. In this research, the researcher relied on the quasi-experimental method, where the students were divided into two groups: an experimental group that used the Block method to teach vocabulary, and a control group that relied on traditional methods of education. The number of students in each group was 19 students. Data were collected through tests before and after applying the educational method, in addition to questionnaires and direct observation. The results of the analysis showed that there was a statistically significant difference between the performance of students in the experimental group and the control group, as the experimental group achieved a significant improvement in vocabulary acquisition. After the researcher analyzed the data, he arrived at the averages of the two tests, the pre-test and the post-test. Based on the average results of the experimental group at a value of 89 and the average results of the control group at a value of 63, this indicates that the average results of the experimental group are greater than the average results of the control group. I analyzed the data using the t-test rule, the t-test result0(It is 7.2, so the table is at a significance level of 5% at a value of 1.677 and a significance level of 1% at a value of 2.407, and this indicates that the null hypothesis)H0(The alternative hypothesis is rejected)Ha) is acceptable. This means that the use of the Blockit method in teaching vocabulary from the perspective of the language strengthening program for students in this school is statistically significant. Keywords: Blooket, Vocabulary Teaching, Language Strengthening Program. مستخلص البحثهد? هذا البحث إلى الكش? عن ?عالية استخدام وسيلة بلوكيت (Blooket) ?ي تعليم الم?ردات العربية لدى تلاميذ مدرسة بمبانجونان المتوسطة الإسلامية ?ي تانجرانج. تزامن هذا البحث مع تطبيق برنامج تقوية اللغة العربية ?ي المدرسة، حيث يسعى البرنامج إلى تحسين مهارات اللغة العربية لدى التلاميذ. اعتمد الباحث ?ي هذا البحث على المنهج شبه التجريبي، حيث تم تقسيم التلاميذ إلى مجموعتين: مجموعة تجريبية استخدمت وسيلة بلوكات ?ي تعليم الم?ردات، ومجموعة ضابطة اعتمدت على الطرق التقليدية ?ي التعليم. بلغ عدد التلاميذ ?ي كل مجموعة ١٩ تلميذًا. تم جمع البيانات من خلال الاختبارات قبل وبعد تطبيق الوسيلة التعليمية، بالإضا?ة إلى الاستبيانات والملاحظة المباشرة. أظهرت نتائج التحليل أن هناك ?رقًا دالاً إحصائيًا بين أداء التلاميذ ?ي المجموعة التجريبية والمجموعة الضابطة، حيث حققت المجموعة التجريبية تحسنًا كبيرًا ?ي اكتساب الم?ردات. وبعد أن قام الباحث بتحليل البيانات، وصل إلى متوسطي الاختبارين الاختبار القبلي والاختبار البعدي. انطلاقا من متوسط نتائج المجموعة التجريبية على قيمة ٨٩ ومتوسط نتائج المجموعة الضابطة على قيمة ٦٣ حتى تدل على أن نتائج المتوسطة للمجموعة التجريبية أكبر من متوسط نتائج المجموعة الضابطة. وتوصلت إلى تحليل البيانات بقاعدة اختبار "ت" نتيجة ت الحسابية (t0) هي ٧،٢ ?الجدول عند مستوى دلالة ٥% على قيمة ١،٦٧٧ ومستوى دلالة ١% على قيمة ٢،٤٠٧ وهذه دلت أن ال?رضية الص?رية(H0) مر?وضة وال?رضية البديلة (Ha) مقبولة. وهذا يعني أن استخدام وسيلة بلوكيت ?ي تعليم الم?ردات من منظور برنامج تقوية اللغة لدى تلاميذ هذه المدرسة دال إحصائيا.  الكلمات الم?تاحية: وسيلة بلوكيت، تعليم الم?ردات، برنامج تقوية اللغة.